2011
DOI: 10.1007/s10930-011-9384-3
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Protein Adsorption onto Synthesis Nano-Hydroxyapatite

Abstract: Adsorption of human serum proteins (Albumin and total protein) onto high purity synthesis nano-hydroxyapatite (HA), Ca₁₀(PO₄)₆(OH)₂, has been studied in a wide temperature range by UV-visible spectrophotometer. Adsorption isotherm is basically important to describe how solutes interact with adsorbent, and is critical in optimizing the use of adsorbent. In the present study, the experimental results were fitted to the Langmuir, Freundlich, Temkin and Dubinin-Radushkevich (DR) models to obtain the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The results demonstrated that MHA had a greatly improving protein loading capacity, nearly double that of HA. A number of factors are important in determining the amount of protein adsorbed on surfaces [6,10,16,17,20]. A higher surface area generally corresponds to a higher amount of protein adsorption [10,16].…”
Section: Quantity Of Protein Adsorption Depended On Timementioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that MHA had a greatly improving protein loading capacity, nearly double that of HA. A number of factors are important in determining the amount of protein adsorbed on surfaces [6,10,16,17,20]. A higher surface area generally corresponds to a higher amount of protein adsorption [10,16].…”
Section: Quantity Of Protein Adsorption Depended On Timementioning
confidence: 99%
“…Hydroxyapatite particles [HA, Ca 10 (PO 4 ) 6 (OH) 2 )] with various morphologies and surface properties have been investigated as protein delivery device due to their biocompatible, nontoxic, and noninflammatory properties [11,[14][15][16][17]. Protein loading on HA is carried out by surface physical adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 45°C, the adsorption was efficient, and there was a slight increase in the adsorption capacity by about 20% because of the increasing diffusion rate into the microcomposites [poly(EGDMA) had a negligible adsorption capacity toward IgG]. An increase in the temperature increased the adsorption capacity of the porous and spherical HA microcomposites because of the endothermic and spontaneous behavior of the adsorption process, as discussed by Mohsen Nia et al…”
Section: Resultsmentioning
confidence: 95%
“…[1617] In addition, hydroxyapatite has been used as an adsorbent for a wide range of ions, small molecules, and macromolecules. [1819] Nano-hydroxyapatite (n-HAp) exhibits a significant adsorption capacity owing to its relatively large surface area[20] and was found to be a superior sorbent because of its low cost, availability, and high defluoridation capacity, as previously reported by Sairam Sundaram et al . [21] n-HAp has also received significant attention for application in medicine and dentistry.…”
Section: Introductionmentioning
confidence: 97%